The importance of energy cooperation between Kazakhstan and Russia within the framework of the Eurasian Economic Union (EAEU) (Journal of history, 2020)
Problems and perspectives for the development of energy relations between Kazakhstan and Russiaare becoming relevant in the context of reforming the Kazakhstani economy and globalization of theworld economy, which dictate the growing interdependence and interaction of national economies. Thecharacter of the emerging new system of global and regional world order is especially pronounced inthe Eurasian region, which has become important and dynamic from a geopolitical and economic pointof view. The geopolitical situation around this region is characterized by a combination and clash of nationalinterests of the main centers of the world economy and policy, such as USA, EU, Russia and China.The purpose of the article is to analyze the bilateral relations of the EAEU member countries – Russiaand Kazakhstan in the energy sector in the new geopolitical conditions. In accordance with the goal, thefollowing tasks were set: to reveal the specific features and imperatives of energy cooperation betweencountries; identify the reasons for the interest of Russia and Kazakhstan in the integration interaction inthe field of energy policy, identify priority areas for the development of energy interaction.